THE BALAKRISHNAN-ALPHA-SKEW-NORMAL DISTRIBUTION: PROPERTIES AND APPLICATIONS: BASN - Hazarika, Partha Jyoti; Shah, Sricharan; Chakraborty, Subrata (Malaysian Journal of Science, 2020)
In this paper a new type of alpha skew distribution is proposed under Balakrishnan (2002) Mechanism and some of its related distributions are investigated. The moments and distributional properties and some extensions related to this distribution are also studied. Suitability of the proposed distribution is tested by conducting data fitting experiments and model adequacy is checked via AIC and BIC in comparison with some related distributions. Likelihood ratio test is carried out to discriminate between normal and proposed distribution.